Anemia and iron deficiency in compensated and decompensated cirrhosis: Prevalence and impact on clinical outcomes. Issue 9 (26th February 2020) - Paternostro, Rafael; Kapzan, Lea; Mandorfer, Mattias; Schwarzer, Remy; Benedikt, Schaefer; Viveiros, André; Bauer, David; Ferlitsch, Monika; Zoller, Heinz; Trauner, Michael; Ferlitsch, Arnulf
Abstract: Background and Aim: Iron deficiency anemia (IDA)is the leading cause of anemia worldwide. Data on prevalence and clinical impact of anemia in cirrhosis are scarce. Aim was to report on the following:(i) prevalence of anemia and IDA in cirrhosis and (ii) its possible impact on clinical outcomes. Methods: Consecutive cirrhotic patients from a prospective registry study were included. Anemia was defined as hemoglobin concentration ≤ 12 g/dL. IDA was defined as Hb ≤ 12 g/dL + transferrin‐saturation < 20%. Follow up for hepatic decompensation and mortality started with study inclusion and terminated in December 2017. A retrospective validation cohort of 1244 patients was used to validate our findings. Results: Two hundred forty‐two patients with compensated ( n  = 53 [21.9%]) and decompensated (n = 189 [78.1%]) cirrhosis were included. Anemia was present in 128 patients (52.9%); of those, 63 (49.2%) had IDA. Prevalence of anemia increased with Child–Pugh Score (CPS; A: 26.5%, B: 59.2%, C: 69%; P  < 0.001) and with decompensated cirrhosis(62.4% vs 18.8%, P  < 0.001). Within anemic patients, a higher proportion of patients in CPS A/B vs C (73% vs 35%; P  = 0.025) and in compensated cirrhosis (80% vs 46.6%; P  = 0.043) were found with IDA. Model for End‐Stage Liver Disease (MELD) scores were significantly lower in patients with IDA (14.4 vs 17.9 non‐ID‐anemia; P  = 0.005). Similar results were found in the validation cohort: median MELD (16[8–28]non‐IDA vs 12 [7–23] IDA; P  < 0.001) and within anemic patients IDA was more common in patients with MELD <15 (58%) versus >15 (24%, P  < 0.001). Anemia was associated with a significant risk for hepatic decompensation and/or mortality both in the validation (aSHR: 1.65, P  = 0.008) and in the derivation cohort (aSHR: 2.11, P < 0.001) and an independent risk factor for hepatic decompensation and/or mortality in compensated patients (aHR: 4.91, P  = 0.004). Conclusion: Anemia is highly prevalent in cirrhosis. In compensated cirrhosis, CPS A/B, and low MELD, IDA seems to be the most likely reason for anemia. Furthermore, anemia is associated with a significant risk for hepatic decompensation or mortality during long‐term follow up.